SPCR-02 NEUROCOGNITIVE FUNCTION IN PATIENTS WITH LEPTOMENINGEAL METASTASIS TREATED WITH PROTON CRANIOSPINAL IRRADIATION. (5th August 2022) - Correa, Denise; Koch, Adrian; Baser, Raymond; Pentsova, Elena; Wolden, Suzanne; Imber, Brandon; Boire, Adrienne; Yang, Jonathan
Abstract: BACKGROUND: Proton craniospinal irradiation (pCSI) as a potential treatment for patients with solid tumor leptomeningeal metastasis (LM) is being assessed in a phase II randomized study comparing it with photon involved-field radiotherapy (RT). We report the preliminary results of prospective neurocognitive function in a subset of patients treated with pCSI. METHODS: Patients with LM and without evidence of CNS disease progression completed standardized neurocognitive tests of attention and working memory, executive function, and verbal memory at baseline (pre-pCSI), and 3 and 6 months post-pCSI. All patients received chemotherapy (baseline and follow up) and memantine (follow up). Means across the three timepoints were estimated for each neurocognitive test score using a linear mixed model (LMM) predicting the score by timepoint. Mean changes between pairs of timepoints were similarly estimated from the LMMs and tested for statistical significance using model-based contrasts. RESULTS: Baseline, 3-month and 6-month neurocognitive data were available for 12, 11, and 8 patients, respectively. Linear mixed model analyses showed a significant decline in graphomotor speed (Trails A, p=0.03), verbal learning (HVLT-R Total Learning, p<0.001), and verbal recognition memory (HVLT-R Discrimination, p=0.03) from baseline to 3 months post-pCSI, with scores remaining stable at 6 months post-pCSI. There was a significant decline in timed set-shifting (Trails B, p=0.04) from baseline to 6 months post-pCSI. There were no significant changes in attention and working memory over the follow-up period. CONCLUSION: Preliminary results in a subset of patients showed a decline in graphomotor speed and verbal memory at 3 months and executive function at 6 months post-pCSI, possibly related to the early adverse effects of RT. These results are overall consistent with findings in other populations treated with whole-brain RT. However, there was no change in attention and working memory and most cognitive domains remained stable at six months with pCSI.